Software database project : project B - Liew, Yi Fei (Nanyang Technological University, 2020)
Students of NTU EEE often participate in many extra-curricular activities like workshops and hackathon camps. This is, however, not reflected in any of the student’s transcripts or school records, and they are often left without any official verification of their attendance. Students participating in these activities are also often not given any official credit for their participation due to the lack of a centralised system from the EEE faculty office. In this project, we explore the many applications that could arise from having this centralised system that would help students keep track of their extra-curricular activities, skillsets acquired from participation in said activities among others that will be elaborated on further below. This will be achieved by developing both the front-end and back-end infrastructure using a variety of tools; React, React Native, Html/CSS/JS for the front-end applications and Node.js with MySQL for the back-end server infrastructure. This paper will elaborate upon the back-end server set-up to support the various student-led development of front-end applications using the data in the database. The development of the back-end infrastructure has met the requirements of the various front-end application requirements and has been set up to allow for further expansion of both data-sets support for future applications requiring the back-end server.